Aeroacoustic simulation of a complete H145 helicopter in descent flight - Kowarsch, U.; Ohrle, C.; Keßler, M.; Krämer, E. (My University, 2015)
In the past years, the aeroacoustic noise emission of a helicopter became one of the most important, but also challenging issues in helicopter development. The blade vortex interaction phenomenon is one of the dominant phenomena characterizing the helicopter's aeroacoustic footprint, which is insufficiently predicted by low fidelity computational methods. For a high fidelity noise prediction of a helicopter configuration, a multidisciplinary CFDCSD- CAA tool chain has been established at the Institute of Aerodynamics and Gas Dynamics of the University of Stuttgart. With higher order CFD computed noise generation at the near field and the noise convection using a Ffowcs-Williams Hawkings based CAA code, very good agreement to measured aeroacoustic noise in wind tunnel as well as free flight experiments of helicopters is achieved. However, the simulations had been limited to the main rotor's geometry up to now, where some residual deviations to the experiment still exist. In this paper, we present a high fidelity aeroacoustic simulation of a complete helicopter configuration and the benefit compared to an isolated rotor simulation in predicting its aeroacoustic noise emission. Shading and reflection effects are clearly resolved, influencing the behaviour of the helicopter's noise radiation. The simulated aeroacoustic noise emission of the helicopter lies within the experimental variation and shows therefore highly promising results for the next generation of aeroacoustic noise prediction.
Keywords: Aerodynamics